Sustained censorship in NL (2026-06) (Netherlands) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Netherlands. Data sourced from OONI.
Censorship Incident ID: NL-2026-0024. Severity: critical. Confidence: 85%